Muscle immobilization activates mitophagy and disrupts mitochondrial dynamics in mice. (30th April 2016) - Kang, C.; Yeo, D.; Ji, L. L.
Abstract: Aim: Skeletal muscle atrophy following prolonged immobilization (IM) is a catabolic state characterized by increased proteolysis and functional deterioration. Previous research indicates that discord of mitochondrial homoeostasis plays a critical role in muscle atrophy. We hypothesized that muscle IM would activate the ubiquitin‐proteolysis, autophagy–lysosome (mitophagy) pathway, mitochondrial dynamics remodelling and apoptosis partially controlled by the FoxO signalling pathway. Methods: Female FVB/N mice were randomly divided into five groups ( n = 8 each): control (CON), IM with banding of one of the hindlimbs for 1, 2 and 3 weeks (1w‐, 2w‐ and 3w‐IM) and 2w‐IM followed by 1 week of remobilization (RM). Results: Mitochondrial density and DNA copies in tibialis anterior (TA) muscle were reduced by approx. 80% ( P < 0.05 for 2w‐IM; P < 0.01 for 3w‐IM), along with activation of FoxO3a, atrogin‐1 and MuRF1 following 2w‐ and 3w‐IM ( P < 0.01). Protein markers of autophagy/mitophagy, such as beclin 1 (approx. 2.7‐fold; P < 0.01), LC3, ubiquitin‐binding adaptor (approx. 1.47‐fold; P < 0.01), Rheb (approx. 1.9‐fold; P < 0.05) and parkin (approx. 70%; P < 0.05), were all increased by IM and remained activated after RM, whereas BNIP3 and PINK1 levels were decreased by IM ( P < 0.05), but elevated upon RM ( P < 0.01). IM decreased Mfn2 expression (approx. 50%; P < 0.01) and increased Fis‐1 expression (approx. 2.4‐fold; P < 0.05). Muscle apoptosis indicator Bax/Bcl2 ratio was elevated at 2w‐ to 3w‐IM (approx. 3.7‐fold; P < 0.01), whereas caspase‐3 activity was five‐ to sixfold higher ( P < 0.01) and remained threefold higher above CON ( P < 0.05). Conclusion: Our data indicate that IM‐induced mitochondrial deterioration is associated with altered protein expressions in the autophagic/mitophagic pathway, more fragmented mitochondrial network and activation of apoptosis partly under the influence of FoxO3 activation.